Avaliação da implementação da tecnologia educativa “Corpo Articulado”, com adolescentes do ensino fundamental de uma escola estadual do oeste do Paraná - Hernandes, Karen Peres (2020)
It is a research with a quantitative and qualitative approach, of an almost experimental type, which evaluated the implementation of the educational technology “Articulated Body”, produced and validated in a previous study entitled “Production and validation of educational technology with adolescents”. The educational technology consists of a pedagogical artifact composed of three overlapping boxes with independent rotation, measuring 1,50 m in height and 40 cm in width. Each box has four illustrated faces, two of which have physical characteristics related to female biological sex and two to male biological sex, representing the initial and final phase of puberty and adolescence, with regard to anatomical characteristics. It composes the use of educational technology, the narration of the true story of a transsexual man called “The Maria who has always been Alex”, described and given in a previous study, by the transsexual subject himself. Its general objective: to evaluate the use of the educational technology “Articulated Body” with teenagers of the ninth year of a state school of elementary and high school in the West of Paraná. For data collection, adolescent subjects were divided into two groups: control group and educational technology group. This occurred in three stages for both groups, the pre-test prior to the educational intervention, the immediate post-test after the intervention and, late post-test, 16 days after the intervention. To this end, an instrument was developed in the format of a structured questionnaire, containing 15 closed questions, divided into three blocks of five questions. This was sent to the validation process by expert judges, in order to judge its consistency in relation to the proposed objectives. The daily field instrument was also used as a resource to expand the range of observations and clarify the data collected. The study took place in a state school of elementary and high school in western Paraná. Statistical data were analyzed using the Chi-square test for independence, with α = 5% of statistical significance. According to the statistical analysis, when comparing the pretest of the control group with the pretest of the educational technology group, the groups were considered statistically equal. The same was observed when comparing the data of immediate post-test and of late posttest between the groups showing that there was no greater learning in the educational technology group as expected. However, the records from the field diaries suggest greater interaction and participation of adolescent subjects in the educational technology group.